Coping Aktif Stress Pengasuhan Orangtua dengan Anak Retadarsi Mental: Literature Review - Milandah Maulina (Humanitas (Jurnal Psikologi), 2021)
The presence of childern being God’s gift to parents and family. Parents are responsible for protect and take care of their child. However sometimes it might beyond expectation, disturbance occur such as mental retardation. This makes the responsibility of parents extra and bring difficult situation as well as parenting stress experience. Hence, efforts to handle the stress of parenting for children with mental retardation are needed because of the presence of parents to help meet their limitations. Active coping can be an effort to actively find ways to overcome the influence of the source of pressure. The aims of this article writing to determine the effectiveness of active coping with stress parenting with mental retardation children. This article is based on literature and journal from several sources such as Garuda Portal, Google Scholar. The results of the literature review revealed that there was a positive relationship between parenting stress and mentally retarded children and the right effort to reduce parenting stress was active coping. There are various forms of active coping, namely the ability in problem solving skills, reducing pressure, self-acceptance and support. In that way, parents will be helped in reducing the difficulty of parenting mental retardation children with active coping which focused on behavioral patterns and cognitive. Limited research that has been done in providing knowledge related to handling stress of parenting mental retardationd children illustrates that the positive attitude of parents in an attempt to reduce the level of parenting stress by selecting active coping is the right effort. Taking active handling steps or solving problems will make the stressful conditions of parenting gradually lessen. Parents will think more optimistically regarding the future of mental retardation children. Keywords: Active Coping, Parenting Stress, Mental Retardation